Entacapone’s therapeutic potential in renal fibrosis by targeting miR-34a/TGFβ1/Smad2 signaling: an experimental rat model study - Yosra M. Magdy; Sherif A. Kamar; Tamer M. M. Abuamara; Yomna M. Tamim; Hayam Ateyya; Marwa Tarek; Nehal Samir; Reham Hussein (Future Journal of Pharmaceutical Sciences)
Abstract Chronic kidney disorder is a rising danger to health that affects a significant percentage of older adults, and a crucial stage in its development is fibrosis. MicroRNAs and transforming_ growth factor-β1(TGF-β1) /SMAD2 signal pathway significantly regulate this process. miR-34a promotes extracellular matrix (ECM) deposition and inhibits B cell lymphoma-2 (Bcl-2), a target gene with antifibrotic properties shown to protect against renal fibrosis in animal models. Currently, several drugs, including entacapone, have been reported to suppress miR-34a activation. Experimental model of Carbon- tetrachloride (CCl4)-induced renal fibrosis revealed elevated serum levels of urea and creatinine, an increased urinary microalbumin-to-creatinine ratio, deterioration of the antioxidant-oxidant balance, an increase in TGF-β1 in renal tissue, and increased renal miR–34a–SMAD2 expression were observed, accompanied by decreased expression of Bcl-2. Entacapone holds reno-protective promises likely via its anti-inflammatory-antioxidant effects in CCl4-induced renal fibrosis by favorable modulation of miR-34a /TGF-β1/SMAD2 Signaling Pathway.